2020
DOI: 10.1503/jpn.190088
|View full text |Cite
|
Sign up to set email alerts
|

Indirect frontocingulate structural connectivity predicts clinical response to accelerated rTMS in major depressive disorder

Abstract: Background: Repetitive transcranial magnetic stimulation (rTMS) is an established treatment for major depressive disorder (MDD), but its clinical efficacy remains rather modest. One reason for this could be that the propagation of rTMS effects via structural connections from the stimulated area to deeper brain structures (such as the cingulate cortices) is suboptimal. Methods: We investigated whether structural connectivity-derived from diffusion MRI data-could serve as a biomarker to predict treatment respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Second, longitudinal changes in cortical thickness between T1 and T2 were significantly correlated with the direct clinical responses and these changes in thickness showed predictive potential for the delayed clinical effects, measured at T4. The caudal part of the cingulate cortex has previously been linked to the response to MDD treatment ( 11 , 31 , 32 ). Interestingly, using the same dataset, it was shown that indirect structural connections (derived from diffusion weighted MRI data) between the stimulation site in the left DLPFC and the right cACC was significantly correlated with the direct clinical responses ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, longitudinal changes in cortical thickness between T1 and T2 were significantly correlated with the direct clinical responses and these changes in thickness showed predictive potential for the delayed clinical effects, measured at T4. The caudal part of the cingulate cortex has previously been linked to the response to MDD treatment ( 11 , 31 , 32 ). Interestingly, using the same dataset, it was shown that indirect structural connections (derived from diffusion weighted MRI data) between the stimulation site in the left DLPFC and the right cACC was significantly correlated with the direct clinical responses ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high interindividual heterogeneity of clinical effectiveness underscores the pressing need for biomarkers to predict treatment outcome. Previous studies showed promising results using measures derived from resting‐state functional MRI (rs‐fMRI) ( 8 , 9 , 10 ) or diffusion weighted MRI (dMRI) ( 11 ). However, these biomarkers require extensive imaging protocols that are not always available in clinical settings, need specialized data processing, and are costly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, stimulation intensity, location of stimulation, position of stimulation and number of sessions and stimuli potentially influence the occurrence of (serious) AE. In addition, patients specific factors like age, medication use, and brain morphology (e.g., functional connectivity and neurodegeneration) will also influence the occurrence of (serious) AE 35 . Consistent reports on AE are needed to describe such potential relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients specific factors like age, medication use, and brain morphology (e.g., functional connectivity and neurodegeneration) will also influence the occurrence of (serious) AE. 35 In a study population with 472 adults receiving HF-rTMS at the DLPFC, 9.7% reported headache, 9.3% experienced scalp discomfort, 1.9% facial twitching, 1.5% tears in their eyes, 1.3% local erythema, 2.5% drowsiness, and 4.7% reported other AE. These percentages were lower in the study population of 109 adults receiving LF-rTMS at the DLPFC of the meta-analysis of Slotema and colleagues.…”
Section: Summary Of Evidencementioning
confidence: 96%